AB0406 Effect of Adalimumab and Impact of Disease Activity and Functional Impairment on Work Instability in Patients with Rheumatoid Arthritis. (10th June 2014) - Emery, P.; Smolen, J.; Ganguli, A.; Meerwein, S.; Bao, Y.; Kupper, H.; Chen, N.; Karunaratne, M.; Kavanaugh, A.
Abstract : Background: In patients (pts) with Rheumatoid Arthritis (RA), adalimumab (ADA) plus methotrexate (MTX) treatment is associated with greater improvements in clinical, patient-reported, and work related outcomes compared to MTX monotherapy. Objectives: To evaluate the effects of ADA+MTX versus PBO+MTX on work instability, and to assess the impact of disease activity and functional impairment on work instability. Methods: A post-hoc analysis at week (wk) 26 and wk 24 from the OPTIMA 1 and PROWD 2 trials, respectively, was conducted for employed pts with baseline RA-WIS score ≥10. Work instability and work productivity were assessed using the RA-Work Instability Scale (RA-WIS) and the Work Productivity and Activity Impairment Questionnaire (WPAI), respectively. Correlation analyses between the change in RA-WIS scores and changes in HAQ-DI, DAS28 and CDAI, were performed to assess the impact of disease activity and functional impairment on work instability (job insecurity due to a mismatch of functional ability and job demands). Chi-square tests assessed treatment group differences in pts with improvements of ≥1 risk category in the WIS score (>17, ≥10 to ≤17, and <10 representing high, medium, or low risk category for job loss respectively), and clinically meaningful improvements by ≥5, ≥7, or ≥9 points in the total WIS score. Missing values were imputed using non-responder imputation for WIS responders and last observation carried forward for all continuous variables. Correlations were assessed using Spearman rank. Mean change in WPAI was assessed between treatment groups using ANCOVA. Results: At baseline, 320/1032 pts in OPTIMA and 124/148 in PROWD, were employed with RA-WIS score ≥10. In both studies, mean DAS28 of 6.1, mean HAQ-DI of 1.6 and mean RA-WIS score of 16.8 at baseline indicate high disease activity, substantial physical disability and medium to high risk for employment loss. In OPTIMA, pts receiving ADA+MTX vs. PBO+MTX had significantly (p<0.05) greater improvements in the RA-WIS (mean change of -7.22 vs. -5.23, respectively). Significantly (p<0.05) more pts in the ADA+MTX group vs. PBO+MTX improved in ≥1 risk category (58% vs. 47%), and improved by ≥5 (55% vs. 43%), ≥7 (47% vs. 35%), and ≥9 (42% vs. 26%) points in the WIS score. These trends were also seen in PROWD, which had smaller sample size. Significant correlations of changes in RA-WIS with changes in HAQ-DI, DAS28, and CDAI (0.653, 0.499, and 0.582, respectively; p<0.0001) indicate that both functional impairment and disease activity are linked to work instability. In OPTIMA, pts receiving ADA+MTX showed a significant (p<0.05) change in percentage points from baseline, vs. PBO+MTX, in activity impairment, presenteeism, and overall work impairment (-32.0 vs. -23.7, -24.6 vs. -17.1, -27.3 vs. -18.3, respectively). Conclusions: Among early RA pts with elevated risk of employment loss, compared with PBO+MTX, ADA+MTX therapy was associated with a significant and clinically meaningful reduction in work instability. Work instability was correlated to functional impairment and disease activity. References: Kavanaugh A, et al. Ann Rheum Dis 2013; 72:64-71. Bejarano V, et al. Arthritis Rheum 2008;59(10):1467-74. Acknowledgements: AbbVie sponsored the studies, participated in study design, data collection, analysis and interpretation; and in the writing, reviewing, and approval of the final version. Medical writing was provided by Jessica L. Suboticki, PhD, of AbbVie. Disclosure of Interest: P. Emery Grant/research support: AbbVie Inc., Pfizer, Novartis, BMS, and Roche, Consultant for: AbbVie Inc., Pfizer, MSD, UCB, Roche, Novartis, and BMS, J. Smolen Grant/research support: AbbVie Inc., Amgen, AstraZeneca, BMS, Celgene, Centocor-Janssen, Glaxo, Lilly, Pfizer, MSD, Novo-Nordisk, Roche, Sandoz, and UCB, Consultant for: AbbVie Inc., Amgen, AstraZeneca, BMS, Celgene, Centocor-Janssen, Glaxo, Lilly, Pfizer, MSD, Novo-Nordisk, Roche, Sandoz, and UCB, A. Ganguli Shareholder of: AbbVie, Employee of: AbbVie, S. Meerwein Shareholder of: AbbVie, Employee of: AbbVie, Y. Bao Shareholder of: AbbVie, Employee of: AbbVie, H. Kupper Shareholder of: AbbVie, Employee of: AbbVie, N. Chen Shareholder of: AbbVie, Employee of: AbbVie, M. Karunaratne Shareholder of: AbbVie, Employee of: AbbVie, A. Kavanaugh Grant/research support: AbbVie Inc., Amgen, Astra-Zeneca, BMS, Celgene, Centocor-Janssen, Pfizer, Roche, and UCB, Consultant for: AbbVie Inc., Amgen, Astra-Zeneca, BMS, Celgene, Centocor-Janssen, Pfizer, Roche, and UCB DOI: 10.1136/annrheumdis-2014-eular.1128